Effects of administration of melatonin on prevalence of delirium and duration of stay in patients admitted to neurosurgical intensive care unit – A prospective study - Anu Hansa,; Zulfiqar Ali,; Iqra Nazir,; Altaf Mir,; Zoya Sehar,; Mir Mohsin,; Shahid Ahmad Mir,; Imtiaz Naqash, (Asian Journal of Medical Sciences, 2024)
Background: The occurrence of delirium in patients who undergo elective surgeries is a common occurrence. Multiple studies have assessed the effect of different drugs in various elective procedures to decrease the prevalence of postoperative delirium. The effect of melatonin to decrease the prevalence of delirium and duration of neurosurgical intensive care unit (NSICU) stay in patients undergoing neurosurgery has not been studied previously. The current study aimed to assess the same. Aims and Objectives: To assess the effect of preoperative and postoperative melatonin administration on the prevalence of delirium in patients undergoing elective ventilation in NSICU and to assess the effect of preoperative and postoperative melatonin administration on the duration of stay in NSICU. Methods and Methods: In this prospective observational study, 60 patients undergoing various neurosurgical procedures and admitted to NSICU were included. The patients were divided into two groups: one group received a placebo (Group P- tablet Sugarfree containing Aspartame) and another group received a tablet of melatonin 3 mg (Group M) in the preoperative and postoperative period. The effect of melatonin on the prevalence of delirium and duration of NSICU stay in these two groups was observed. Results: A decreasing trend of delirium was noted in both groups (Group M and Group P) with no statistical significance. A decreased prevalence of delirium was observed in patients of group M (33.3%) at the end of 12 h post-extubation compared to Group P (43.3%). The mean duration of stay for the patients in NSICU in Groups M and P were 2.7 and 3.2 days, with the range (1–14 Days) in Group M and Group P (1–20 days), respectively. Conclusion: Although there was a decreased prevalence of delirium and a decrease in the mean duration of the intensive care unit stay in patients who received oral melatonin, these beneficial effects did not show any statistical significance once compared with the control group.